Architectural Design of Public Service Application Mojorejo 01 Elementary School, Madiun City - Mumtahana, Hani Atun; Andria, Andria; Asnawi, Noordin; Malashandy, Malvin (Association for Scientific Computing, Electronics, and Engineering (ASCEE), 2025)
The delivery of information to the general public is one of the business processes that need to be developed at Mojorejo 01 Elementary School, Madiun City. The school profile website can be used as a medium for distributing school information, so that the general public, guardians, students, and teachers can obtain information on time. In addition, information about guidance and counseling from student achievements needs to be published to increase the school's excellence. In this study, an architectural design was designed for the development of a school profile website and e-counseling application to support the business processes at Mojorejo 01 Elementary School, Madiun City. The development of architectural design includes several stages of business process architecture design, data and information architecture, application architecture, and technology architecture. The results of the study are in the form of architectural design and recommendations for developing school web applications and e-counseling that can be used by schools and developers in developing applications. To assess the suitability of the architectural design to the needs of the business process and business processes of Mojorejo 01 Elementary School, an evaluation has been carried out with a result of 83.8%, which shows that the architectural design can be applied in application development.